Sertifikasi untuk Meningkatkan Profesionalisme Guru: Sertifikasi untuk Meningkatkan Profesionalisme Guru - Yopa Taufik Saleh (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2016)
The low quality of education in Indonesia cannot be separated from the low quality of teachers. To achieve qualified teachers, so it needs the effective of teacher management start from the appointment, the placement, the induction, the welfare, and the teacher professional development. The certification program is one of government programs to increase the teachers’ professionalism. However, this certification program was responded vary by teachers. Some of them respond it with sincerity and other consider it just as other policies. Meanwhile, the teacher certification could be interpreted as the government's efforts in providing education certificates to the teachers and lecturers who have met certain requirements, including academic qualifications, competence, professional in the field of education with the aim to increase learning motivation and teachers’ welfare. Certification is a government program in increasing the teachers’ motivation and professionalism. Thus, it is expected to be able to solve any problems in education world.